République de Côte d’Ivoire 2021-2030 - Sustaining High, Inclusive, and Resilient Growth Post COVID-19 : A World Bank Group Input to the 2030 Development Strategy - World Bank (World Bank, Washington, DC, 2021)
This report, initiated at the request of His Excellency President Alassane Ouattara to Hafez M. H. Ghanem, the World Bank Group Regional Vice President for Eastern and Southern Africa, is the first country application of the new regional strategy, Supporting Africa’s Transformation. Albert Zeufack, the Chief Economist of the World Bank Group Africa Region, led a team to synthesize knowledge and experience from Côte d’Ivoire and across the world. The report incorporates the perspective of the new International Development Association agenda, Jobs and Economic Transformation, and addresses three operational objectives for Côte d’Ivoire: create sustainable and inclusive growth by maintaining macroeconomic stability, fighting corruption, advancing digital transformation, and maximizing private finance; strengthen human capital by empowering women, reducing child mortality and stunting, and improving education, health, and social protection; build resilience against fragility and climate change. The National Development Plan 2016-20 consolidated promarket reforms and reaffirmed the ambition to reach upper-middle-income status. Côte d’Ivoire is embarking on a strategy to sustain strong gross domestic product (GDP) growth through 2030 while rapidly reducing poverty. Côte d’Ivoire’s aspiration of becoming an emerging market economy with low levels of poverty requires a long period of strong and inclusive growth. The report analyzes growth trajectories and identifies the investments needed to achieve and sustain desired levels of growth, along with the corresponding financing needs. It discusses the opportunities presented by the country’s surplus labor, young population, and huge diversification potential.